A study of the reasons of students in their pursuit of the MLIS degree and their choice of MLIS school - Torres, Efren M., Jr.; Faderon, Rosalie B. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2002)
Having a master's degree is truly an advantage. Many people are starting to realize its importance for it really gives them security whether financially or morally. One of the numerous master's title is the Master of Library and Information Science which is considered as the only graduate degree level in the field of library and information science.
The researcher's purposes, in doing the study, were: to determine the reasons of the students in pursuing an MLIS degree and in choosing a particular MLIS school; to know if the MLIS students of the different schools concerned have similar views regarding their pursuit of the MLIS degree and their choice of an MLIS school; and to know the answers of the MLIS students regarding the practicality of taking an MLIS degree.
The data gathered were from 74 MLIS students from UP, PNU, UST, and UE. The respondents stated that the primary reason for pursuing the MLIS degree was "to upgrade professional skills" and their number one ranked reason for choosing the MLIS school was "because of curriculum." According to them, taking an MLIS degree is not only practical but also a must. Seventy-two (72) out of the seventy-four respondents (97.30 percent) overwhelmingly answered "yes" to support this.
On the other hand, the following recommendations were offered by the researcher in consonance with the data given by the respondents: evaluating the curriculum if it is globally competitive; better promotion for schools having limited number of enrollees; more subjects about information technology should be included in the curriculum; and consider other factors that can affect the decisions of the students in choosing the library school like having modernized rooms, better facilities and equipment, and updated collections in the library.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines Institute of Library and Information Science -- Graduate students; Degrees, academic